2019
DOI: 10.1111/bpa.12770
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of adenosine A2A receptor and downregulation of GLT1 is associated with neuronal cell death in Rasmussen's encephalitis

Abstract: Rasmussen encephalitis (RE) is a severe pediatric inflammatory brain disease characterized by unilateral inflammation and atrophy of the cerebral cortex, drug‐resistant focal epilepsy and progressive neurological and cognitive deterioration. The etiology and pathogenesis of RE remain unclear. Our previous results demonstrated that the adenosine A1 receptor (A1R) and the major adenosine‐removing enzyme adenosine kinase play an important role in the etiology of RE. Because the downstream pathways of inhibitory A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 66 publications
6
17
0
Order By: Relevance
“…78 Furthermore, our study demonstrated that upregulated A2AR led to downregulation of glutamate transporter GLT-1, and that neuron apoptosis was finally induced. 79 The above results proved that dysfunction of the adenosine system plays a significant role in the pathogenesis of RE, in particular in neuronal damage.…”
Section: Future Therapeutic Directions: Experimental and Clinical Evidencementioning
confidence: 64%
“…78 Furthermore, our study demonstrated that upregulated A2AR led to downregulation of glutamate transporter GLT-1, and that neuron apoptosis was finally induced. 79 The above results proved that dysfunction of the adenosine system plays a significant role in the pathogenesis of RE, in particular in neuronal damage.…”
Section: Future Therapeutic Directions: Experimental and Clinical Evidencementioning
confidence: 64%
“…Epilepsy is associated with altered cellular distribution of adenosine receptors and ADK that may occur as primary or secondary adaptive phenomena 1,2 . Earlier studies utilizing human tissues found enhanced neuronal expression of A 1 R 21 and upregulation of A 2A R in Rasmussen's encephalitis, with A 2A R expression in lesional astrocytes, endothelium, as well as neurons 5 . In TLE, A 2A R expression was primarily co‐localized with hippocampal GFAP‐positive astrocytes but not neuronal markers, showing increased receptor expression compared with postmortem controls 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in adenosine receptors densities and their cellular distribution has been shown in animal models of epilepsy1,2 and human tissues 4‐6 . An imbalance between the inhibitory and excitatory effects of adenosine through differential activation of A 1 R and A 2A R receptors may contribute to temporal lobe epilepsy (TLE) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The A 2A R overactivation associated with brain dysfunction and disease is not only sustained by an increased bioavailability of the trigger of A 2A R-ATP-derived extracellular adenosine-but also involves an up-regulation of A 2A R in the afflicted brain areas (reviewed in Cunha, 2016). Indeed, an increased density of cortical A 2A R has been reported in animal models of epilepsy (Rebola et al, 2005;Cognato et al, 2010;Canas et al, 2018;Crespo et al, 2018), Rasmussen's encephalopathy (He et al, 2020), TBI (Zhao et al, 2017), AD (Espinosa et al, 2013;Viana da Silva et al, 2016;Silva et al, 2018), Lyme neuroborreliosis (Smith et al, 2014), ALS (Seven et al, 2020), or chronic stress/depression (Kaster et al, 2015;Machado et al, 2017), as well as in the diseased human brain (Albasanz et al, 2008;Temido-Ferreira et al, 2020). Likewise, A 2A R levels are also increased in the cerebellum of Machado-Joseph's ataxic mice (Gonçalves et al, 2013) and in the amygdala or fear-conditioned mice (Simões et al, 2016).…”
Section: Up-regulation Of Adenosine a 2a Receptors In Brain Diseasesmentioning
confidence: 99%